Moving Toward Decolonizing and Indigenizing Curricular and Teaching Practices in Canadian Higher Education (LEARNing Landscapes, 2021)
In this reflective paper, I interweave autoethnographic personal narrative and critical self-reflection with theoretical literature in order to engage and wrestle with decolonizing and Indigenizing my teaching and curricular practices in Canadian higher education. Acknowledging that walking this path is challenging, I seek multiple trailheads in an effort to access my hidden curriculum, my complicit knowledge, and unsettling moments that have the potential to transform me. My objective is to critically interrogate myself to prepare for respectfully and appropriately moving toward reconciliation in my relationships with Indigenous colleagues, students, and communities, and in my work as a curriculum maker.
Keywords: Indigenization; higher education; educational development; curriculum; reflective practice